2019
DOI: 10.35381/cm.v6i10.241
|View full text |Cite
|
Sign up to set email alerts
|

El maestro y la educación sostenible 2030

Abstract: El actual artículo de revisión, tiene como propósito analizar el rol del maestro en la educación sostenible 2030, desde una perspectiva documental – analítica. La educación corre el riesgo de perder su esencia al pretender separar lo ético – espiritual de lo académico, al contrario debe ser una triada inseparable, sobre todo en los primeros años de formación del estudiante, los padres y representantes deben girar nuevamente a comprender el rol en conjunto al maestro de educar a sus hijos, el hogar y la escuela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…This may contribute to a certain lack of definition of their professional identity [21], but it is also a challenge for university professors in charge of training these future teachers. Actually, in this study, a solid relationship has been found between research and innovative TPI, suggesting that a number of students have made a move into the assumption of a more elaborate and complex TPI, a new profile of innovative and research-oriented teaching as a function inherent in their role [22].…”
Section: Discussionmentioning
confidence: 64%
“…This may contribute to a certain lack of definition of their professional identity [21], but it is also a challenge for university professors in charge of training these future teachers. Actually, in this study, a solid relationship has been found between research and innovative TPI, suggesting that a number of students have made a move into the assumption of a more elaborate and complex TPI, a new profile of innovative and research-oriented teaching as a function inherent in their role [22].…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, underscoring potential gaps in knowledge and understanding may hinder the effective implementation of sustainable development goals within the university context (UNESCO, 2014(UNESCO, , 2018(UNESCO, , 2020(UNESCO, , 2021. As a consequence, establishing supportive policies and strategies is a must to enable teachers to utilize their full range of abilities to address global challenges, while also emphasizing the importance of restoring the teacher's social standing as a crucial societal cornerstone as Burgos et al (2019) pointed out.…”
Section: Discussionmentioning
confidence: 99%
“…As role models for global citizenship, educators must promote values such as diversity, empathy, and social responsibility, thus, they must enhance their understanding and teaching abilities to meet evolving requirements and curriculum and content effectively since they are at the forefront of education and play a critical role in ensuring real learning experiences (UNESCO, 2018). However, teachers face a variety of challenges to align with the 2030 educational policies, including the need for professional development to enhance their intercultural competence, overcoming institutional barriers to curriculum internationalization, and dealing with resistance to global perspectives from students and colleagues (Burgos et al, 2019), this involves creating policies and strategies to restore the social significance of teachers as a crucial pillar of society to effectively encourage and facilitate IoC and GCED in higher education institutions. Finally, it is worth noting that to establish a positive environment that empowers teachers to effectively teach Education for Sustainable Development (ESD) and GCED, it is essential to gather insights and feedback from various stakeholders, such as individuals and groups from academic and systemic domains (UNESCO, 2020(UNESCO, , 2021.…”
Section: The Crucial Role Of Educators In Shaping Tomorrow's Citizensmentioning
confidence: 99%
See 1 more Smart Citation